2017
DOI: 10.1111/jphp.12720
|View full text |Cite
|
Sign up to set email alerts
|

Safety issues of compounds acting on adenosinergic signalling

Abstract: Objectives Much research has been performed on the field of identifying the roles of adenosine and adenosinergic signalling, but a relatively low number of marketing authorizations have been granted for adenosine receptor (AdR) ligands. In part, this could be related to their safety issues; therefore, our aim was to examine the toxicological and adverse effects data of different compounds acting on adenosinergic signalling, including different AdR ligands and compounds resembling the structure of adenosine. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 127 publications
0
7
0
Order By: Relevance
“…What becomes clear is that while caffeine has rather simple or less complex mechanisms in cases of normal use, in cases of toxicity and especially lethal doses, caffeine becomes a much more complex molecule potentially interacting with several molecular targets which may explain its side effects. For example, its antagonism of GABA(A) could explain the reports of seizures, although others have also pointed out the role of adenosine antagonism as well, with A1 agonism producing anticonvulsant activity and A1 antagonism lowering seizure threshold by increasing the release and activity of excitatory amino acids/neurotransmitters [ 38 , 115 , 116 ].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…What becomes clear is that while caffeine has rather simple or less complex mechanisms in cases of normal use, in cases of toxicity and especially lethal doses, caffeine becomes a much more complex molecule potentially interacting with several molecular targets which may explain its side effects. For example, its antagonism of GABA(A) could explain the reports of seizures, although others have also pointed out the role of adenosine antagonism as well, with A1 agonism producing anticonvulsant activity and A1 antagonism lowering seizure threshold by increasing the release and activity of excitatory amino acids/neurotransmitters [ 38 , 115 , 116 ].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…While some have suggested with at least some evidence that caffeine’s effects at high doses are not due to adenosine antagonism [ 138 ], it is interesting to note that the adenosine A1 receptor antagonist, rolofylline was associated with an increased risk of seizure and stroke in clinical trials. These side effects and lack of efficacy led to its abandonment [ 116 ]. Others have indicated that adenosine antagonism could potentially cause cardiotoxic effects as well and adenosine itself is an anti-dysrhythmic [ 38 , 47 , 139 ].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Adenosine has been widely recognized as an inhibitory modulator of the CNS. 26 It acts as a homeostatic modulator at synapses 26,27 and participates in neurotransmitter release, 28 neuronal excitability, synaptic plasticity, 29 and local inflammatory processes. 30,31 Adenosine is complicated in neurobiology of learning and memory 29,32,33 by overstimulating the N-methyl-D-aspartic acid (NMDA) receptors 34,35 that influence long-term potentiation (LTP) and long-term depression (LTD).…”
Section: Adenosine Receptors and Functions In The Cnsmentioning
confidence: 99%
“…Structure-based molecular modeling has led to the rational design of an impressive panel of potent, highly-selective A 3 AR ligands [8]. For therapeutic application, these synthetic ligands must display good pharmacokinetic properties, as well as excellent A 3 AR binding affinity, selectivity, efficacy and potency [14, 15]. Currently, functional evaluation of these A 3 AR ligands relies mainly on the measurement of Gi protein-mediated signalling using cAMP accumulation assays.…”
Section: Introductionmentioning
confidence: 99%